2020
DOI: 10.4269/ajtmh.20-0892
|View full text |Cite
|
Sign up to set email alerts
|

Traveling into the Abyss: Risk Perception of German Travelers at the Onset of the COVID-19 Pandemic

Abstract: The emergence and international spread of SARS-CoV-2 led to unprecedented challenges for international travelers including health-related concerns and international travel restrictions. Remarkably, overseas travelers consulted at our travel clinic during the first quarter of 2020 were apparently not disconcerted by the evolving pandemic with a continuously high rate of consultations at our center; 85% of travelers did not actively inquire about COVID-19 during the pretravel consultation including individuals w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 2 publications
(2 reference statements)
0
3
0
1
Order By: Relevance
“…As Shamsrizi et al (2020) reported, individuals’ previous travel experience may affect not only their behavioral intentions for traveling, but also their risk perception, knowledge and health protective behavior against COVID-19. Therefore, previous travel experiences (foreign business, foreign leisure, and domestic leisure) in the past 2 years were questioned.…”
Section: Methodsmentioning
confidence: 97%
See 2 more Smart Citations
“…As Shamsrizi et al (2020) reported, individuals’ previous travel experience may affect not only their behavioral intentions for traveling, but also their risk perception, knowledge and health protective behavior against COVID-19. Therefore, previous travel experiences (foreign business, foreign leisure, and domestic leisure) in the past 2 years were questioned.…”
Section: Methodsmentioning
confidence: 97%
“…Although the cognitive-, affective-, psychographic-, and sociodemographic factors associating with their health-related concerns and their health protective behaviors have generally been investigated in previous research, there are a limited number of studies investigating individuals’ traveling behaviors and their health-related concerns and protective behaviors. Shamsrizi et al (2020) reported, from the viewpoint of travel medicine practitioners, that “the vast majority of travelers visiting (their center) did not appreciate the health risks and logistical challenges posed by the evolving pandemic just before the international ban on travel and the near to complete lockdown on international air travel” ( Shamsrizi et al, 2020 , p1640). Their study pointed out the heterogeneous “response to an imminent epidemiological threat” ( Shamsrizi et al, 2020 , p1640) observed among the German population.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Während der COVID-19-Pandemie kam es im Jahre 2020 zu einem beispiellosen Rückgang der internationalen Reisetätigkeit, der durch die nationalen und internationalen Regulationen zur Isolation und Quarantäne und die damit verbundenen starken Einschränkungen internationaler Flugverbindungen erklärt war [3]. Parallel zum Einbruch der internationalen Reisetätigkeit kam es im Jahr 2020 zu einem dramatischen Rückgang der importierten Malariafälle in Deutschland.…”
unclassified